2013
DOI: 10.1603/ec13218
|View full text |Cite
|
Sign up to set email alerts
|

Flight Performance of the Orange Wheat Blossom Midge (Diptera: Cecidomyiidae)

Abstract: The orange wheat blossom midge, Sitodiplosis mosellana (Géhin) (Diptera: Cecidomyiidae), is a chronic wheat pest worldwide. Adult S. mosellana engage in short-distance flight, but also exploit weather patterns for long-distance dispersal. However, little is known about the flight performance of S. mosellana, and the effects of the biotic and abiotic factors that influence its flight activity. In this study, we explored the active flight potential of S. mosellana under various environmental factors using a 26-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…2013 ). At 16°C, 1-d-old adult female S. mosellana Gehin (Diptera: Cecidomyiidae) flew an average of 0.74 km within 24 h with an average speed of 0.16 m/s; while at 24°C they flew on average only 0.28 km within 24 h with an average speed of 0.13 m/s ( Hao et al . 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013 ). At 16°C, 1-d-old adult female S. mosellana Gehin (Diptera: Cecidomyiidae) flew an average of 0.74 km within 24 h with an average speed of 0.16 m/s; while at 24°C they flew on average only 0.28 km within 24 h with an average speed of 0.13 m/s ( Hao et al . 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the flight capacity of B. dorsalis , we tested average flight speed and flight distance of B. dorsalis adult females of various ages on a computer-monitored flight mill, which can provide useful information on the flight capacity of insects ( Cui et al . 2013 , Hao et al . 2013 ).…”
mentioning
confidence: 99%
“…It is expected that some traits such as body size and high resource specialisation are the key factors, which result in a more pronounced negative response to spatial scale (Tscharntke & Brandl, 2004). Therefore, it is possible that small host-plant specialist gall midges (Carneiro et al, 2009), with relatively short active dispersal ranges from 1-7 m for Rhopalomyia californica to 500 m for Sitodiplosis mosellana (Briggs & Latto, 2000;Hao et al, 2013), could be negatively affected by increasing habitat fragmentation. A study on vertical zonation in North western Switzerland indicated that females of M. fagi were capable of fl ying up to the canopy (> 30 m) for oviposition (Kampichler & Teschner, 2002), but greater fl ight distances have not been recorded for this species.…”
Section: Effects Of Urbanisation and Forest Size On Plant Gallsmentioning
confidence: 99%
“…A silica capillary builds the arm where individuals of leafhoppers (Hemiptera: Auchenorrhyncha) are attached. Magnetic floating or magnetic sustenance is commonly used to build flight mills [ 14 , 19 , 20 ].…”
Section: Rationalementioning
confidence: 99%